Pengaruh perbedaan varietas dan zat pengatur tumbuh terhadap pertumbuhan dan perkembangan bawang merah (Allium ascalonicum L.): The effect of different varieties and plant growth regulator on the growth and development of shallot (Allium ascalonicum L.) - Siswadi, Edi; Choiriyah, Nikmatul; Pertami, Rindha Rentina Darah; Nugroho, Setyo Andi; Kusparwanti, Tri Rini; Sari, Vega Kartika (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: Shallots are a horticultural product needed by the Indonesian people, the production of shallots has decreased by 16.54%. The decline in production in 2018 was caused by extreme weather in the first quarter which resulted in a significant decrease in production. The purpose of the study was to determine the interaction between the use of varieties and the administration of ZPT at various concentrations on the growth and development of shallot plants. Methods: The experimental design used a randomized block design (RBD) with 2 factors, namely, the onion variety factor (V1: Bauji variety and V2: Blue Lancor variety) and the concentration of PGR (BAP and GA3) consisting of Z0: control (without PGR), Z1: BAP 50 ppm, Z2: GA3 150 ppm, Z3: BAP 50 ppm + GA3 150 ppm. Results: The results showed that the use of various varieties and concentrations of PGR did not affect the vegetative growth of Shallots. The use of various varieties has a significantly different effect on the generative development of shallot plants. The use of ZPT concentrations did not affect the generative development of plants. Two varieties, namely Bauji and Biru Lancor, were unable to influence the growth and development of shallots in the vegetative and generative phases because of the genetic characteristics of the plants whose function was to characterize each variety. Apart from genetic factors, this is thought to be caused by the degree of suitability of the variety to its environment. Conclusion: The Bauji variety is more suitable to be planted in the lowlands of Antirogo than the Blue Lancor variety.